2012
DOI: 10.1590/s0365-05962012000200012
|View full text |Cite
|
Sign up to set email alerts
|

Contact sensitivity to metals (chromium, cobalt and nickel) in childhood

Abstract: Metals, especially nickel, are the most common contact allergens in children. Recent data has shown increased incidence of allergy in industrialized countries. Sensitization can occur at any age, even in neonates. Costume jewelry, particularly earrings, is linked to increased sensitization to nickel. Sensitization to cobalt often occurs by the use of costume jewelry. The most common source of sensitization to chromium is leather. Due to the absence of a specific therapy, the main treatment is to identify and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 60 publications
0
15
0
2
Order By: Relevance
“…However, these products can be potentially dangerous for children, including especially atopic children. The children's skin is particularly thin, so it is very susceptible to external harmful factors (Brandão and Gontijo, 2012). Toy cosmetics are sold in kits such as eye shadows and lipsticks.…”
Section: Metals In Colour Cosmeticsmentioning
confidence: 99%
“…However, these products can be potentially dangerous for children, including especially atopic children. The children's skin is particularly thin, so it is very susceptible to external harmful factors (Brandão and Gontijo, 2012). Toy cosmetics are sold in kits such as eye shadows and lipsticks.…”
Section: Metals In Colour Cosmeticsmentioning
confidence: 99%
“…There have been no reports of IH to chrome dyes in textiles. Although chromium is a well known contact allergen, fabrics have not been a source of sensitisation (73). A literature review of tex-tile dye dermatitis by Hatch & Maibach (74) similarly reported no cases of ACD owing to after-chrome dyes.…”
Section: Allergy To Textile Dyes and Finishesmentioning
confidence: 99%
“…The individual, who insists on keeping the adornment even with dermatitis, cannot however foresee the development of hypersensitivity. 35 In this investigation, a student had allergic sensitization to nickel confirmed by patch testing.…”
Section: Discussionmentioning
confidence: 97%
“…This knowledge is important in the medical environment because such situations can have serious physical and emotional consequences, and require specific approaches for their prevention and treatment. 1 , 29 , 32 - 35 The aim of this study is to evaluate the prevalence of cutaneous piercing and the ensuing consequences among young medical students.…”
Section: Introductionmentioning
confidence: 99%